Main obstetric complications caused by COVID-19 (Research, Society and Development, 2023)
Objective: to identify the main obstetric complications in pregnant women infected with SARS-CoV-2, in order to improve the health care provided to the mother-fetus binomial. Methodology: The present study is a systematic review of the literature, which was carried out in August 2022, through a search in the Virtual Health Library (BVS) and Google Scholar databases, using the descriptors "Coronavirus", “Pregnant women”, “Obstetric complications” and “Covid-19”. Results: We selected 25 articles, published between 2020 and 2022, among which the most recurrent obstetric and fetal complications associated with COVID-19 were identified. Discussion: The most prevalent laboratory alterations were lymphopenia, increased D-Dimer and C-reactive protein. There was also an increase in the number of cesarean sections, premature births and premature rupture of ovular membranes (PRMO). In addition, infected pregnant women may have fibrin deposition in the placenta, developing a more severe picture of coagulopathy. Conclusion: In view of the above, knowledge of the possible obstetric complications of COVID-19 infection is necessary in order to improve the health care provided to the mother-fetus binomial.